Hannah Arendt – Critical Lives: Hannah Arendt – Critical Lives - Dufraing, An (HannahArendt.net, 2022)
Samantha Rose Hill: Hannah Arendt, London: Reaktion Books, 2021, 232 p. (9781789143799 - Paperback)